2016
DOI: 10.18203/2394-6040.ijcmph20164742
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with tuberculous meningitis: a prospective study from a tertiary care centre in Southern India

Abstract: Background: TB Meningitis is one of the most serious forms of Tuberculosis. Objective of the current study was to assess the clinical outcome of children presented with TB Meningitis in a tertiary care centre in southern India by following them up and assess their present state in terms of neurological deficits, hearing and visual deficits, learning difficulties and day to day performances.Methods: Children between 0 - 15 years diagnosed to have TB meningitis in a 2700 bedded hospital in Tamilnadu, India, duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…van Well et al 32 reported that 16 per cent of the children were normal, 52 per cent had mild sequelae, 19 per cent had severe sequelae and 13 per cent died when followed up after six months. In a study from southern India, children treated for TBM were reviewed after 2 to 7 yr, 46 per cent had behavioural problems, 46 per cent had poor schooling performance, 22 per cent had neurological deficit and 15 per cent had seizure disorder95. Miftode et al 33 reported that children had higher frequency of neurological deficits; however, mortality rates were similar to adults.…”
Section: Discussionmentioning
confidence: 99%
“…van Well et al 32 reported that 16 per cent of the children were normal, 52 per cent had mild sequelae, 19 per cent had severe sequelae and 13 per cent died when followed up after six months. In a study from southern India, children treated for TBM were reviewed after 2 to 7 yr, 46 per cent had behavioural problems, 46 per cent had poor schooling performance, 22 per cent had neurological deficit and 15 per cent had seizure disorder95. Miftode et al 33 reported that children had higher frequency of neurological deficits; however, mortality rates were similar to adults.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with other studies where poor outcome was associated with hydrocephalus, tubercle, and cerebral infarct. 33…”
Section: Discussionmentioning
confidence: 99%
“…Many studies recognise that tuberculous meningitis, a severe complication associated with tuberculosis, can have implications for cognitive development in children. 3436 Data from the present study did not specify the severity of tuberculosis infections in study members, thus limiting comparability with other studies. The studies on the effects of tuberculous meningitis on cognition did not stratify results for each sex, 3436 although in one study mortality in females was higher.…”
Section: Discussionmentioning
confidence: 82%
“…3436 Data from the present study did not specify the severity of tuberculosis infections in study members, thus limiting comparability with other studies. The studies on the effects of tuberculous meningitis on cognition did not stratify results for each sex, 3436 although in one study mortality in females was higher. This indicates a need for more research on the effects of tuberculosis between sexes.…”
Section: Discussionmentioning
confidence: 82%